DISSECTING IMPLICIT MEANING IN TEMBANG DOLANAN: A DISCOURSE ANALYSIS - Abdullah, Asep Abbas; Muhid, Abdul; S.A.P., Rangga Sa’adillah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
This article uses discourse analysis to examine dolanan songs such as Sluku-Sluku Bathok, Cublak-Cublak Suweng, Lir-Ilir, Gundul-Gundul Pacul, and Kloso Bedah. The method used in this research is a descriptive qualitative method so that the data can be described as clearly and objectively as possible by the researchers' subjective views. To avoid bias on the validity of the research results, triangulation was carried out by comparing the researchers' interpretations with some supporting literature. The result of this research is that five dolanan songs contain many meanings. The songs offer a deep meaning about the condition of the environment that grows around it to increase the value of character, good behavior, the environment - especially cleanliness, health, and religious life. The character values are conveyed through satire or humor. Dolanan songs have meanings, both explicit and implicit, about this life. These songs are neatly arranged both in terms of structural both physically and mentally. Javanese children's songs contain poetry filled with language games, such as alliteration, assonance, poetry, and rhythm.